Working Memory and Intelligence The same of Different Constructs? . [article]. - Ackerman Phillip, L.
Several investigators have claimed over the past decade that working memory (WM) and general intelligence (g) are identical, or nearly identical, constructs, from individual-differences perspective. Although memory measures are commonly included in intelligence tests and memory abilities are included in theories of intelligence the identity between WM and intelligence has not been evaluatedcomprehensively. The authors conducted ameta-analysis of 86 samples that relate WM ti intelligence. The average correlation between true score estimates of WM and g is substantially less than unity(p=.479. The authors also focus on the distinction between short term memory and WM with respect tointelligence with a supplemental meta-analysis. The authors discuss how consideration of psychometric and theoretical perspectives better informs. [ the discussion of WM-intelligence relations. (from the author).
Keywords: Psychology-Periodicals.